Modern Approach to Sports Industry Management under Uncertainty - Leonov, Ya. (Економічний вісник Донбасу, 2020)
The article considers the organizational conditions for the functioning of the sports industry, suggests ways to ensure the strategic development of the sports industry in conditions of uncertainty. The possibility of implementing the European model of socio-economic development management in Ukraine is analyzed, it is concluded that it is connected with complex systemic transformations in which a new quality society is formed, the level of business activity and political responsibility of citizens increases, human rights and freedoms are ensured. These changes in the structure and content of civil society inevitably determine changes in the form and essence of public policy in the system of state, territorial and sectoral government. The problem of developing social responsibility of business in Ukraine at the present stage is relevant and of paramount importance. Therefore, state support is necessary for the importance of ethical and socially responsible behavior of organizations, increasing their prestige. The introduction of a system of modern management of the sports industry, the use of best European management practices will increase competitiveness, efficiency and ensure the sustainable development of the sports industry in conditions of uncertainty. Improving the efficiency of interaction in the system "state – community – science – business" and building a socially responsible economic policy, improving the quality of the national management system of the sports industry is one of the main conditions for sustainable socio-economic development of the country as a whole man. У статті розглянуто організаційні умови функціонування спортивної індустрії, запропоновано напрями забезпечення стратегічного розвитку спортивної індустрії в умовах невизначеності. Проаналізовано можливість впровадження європейської моделі управління соціально-економічним розвитком в Україні, зроблено висновок: це пов’язано зі складними системними перетвореннями, в яких формується суспільство нової якості, підвищується рівень ділової активності та політичної відповідальності громадян, забезпечуються права і свободи людини. Ці зміни у структурі та змісті громадянського суспільства неминуче детермінують зміни у формі та сутності державної політики в системі державного, територіального та секторального управління. Проблема розвитку соціальної відповідальності бізнесу в Україні на сучасному етапі є актуальною й має першочергове значення. Тому підтримка держави необхідна для важливості етичної та соціально відповідальної поведінки організацій, підвищення їхньої престижності. Впровадження системи сучасного управління спортивною індустрією, використання кращих європейських практик управління дозволять підвищити конкурентоспроможність, ефективність та забезпечити сталий розвиток спортивної індустрії в умовах невизначеності.
Підвищення ефективності взаємодії у системі «держава – громада – наука – бізнес» та розбудови соціально відповідальної економічної політики, підвищення якості національної системи управління спортивною індустрією є однією з головних умов забезпечення сталого соціально-економічного розвитку країни в цілому, а також основним чинником покращення якості життя людини. В статье рассмотрены организационные условия функционирования спортивной индустрии, предложены направления обеспечения стратегического развития спортивной индустрии в условиях неопределенности. Проанализирована возможность внедрения европейской модели управления социально-экономическим развитием в Украине, сделан вывод: это связано со сложными системными преобразованиями, в которых формируется общество нового качества, повышается уровень деловой активности и политической ответственности граждан, обеспечиваются права и свободы человека. Эти изменения в структуре и содержании гражданского общества неизбежно детерминируют изменения в форме и сущности государственной политики в системе государственного, территориального и секторального управления. Проблема развития социальной ответственности бизнеса в Украине на современном этапе является актуальной и имеет первостепенное значение. Поэтому поддержка государства необходима для важности этической и социально ответственного поведения организаций, повышения их престижности. Внедрение системы современного управления спортивной индустрией, использование лучших европейских практик управления позволят повысить конкурентоспособность, эффективность и устойчивое развитие спортивной индустрии в условиях неопределенности. Повышение эффективности взаимодействия в системе «государство – общество – наука – бизнес» и развития социально ответственной экономической политики, повышение качества национальной системы управления спортивной индустрией является одним из главных условий обеспечения устойчивого социально-экономического развития страны в целом, а также основным фактором улучшения качества жизни человека.